2008
DOI: 10.1007/s11033-008-9305-5
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphism in normal Han Chinese population: frequency and effect on lipid parameters

Abstract: Apolipoprotein E (ApoE) genotypes were studied in order to determine the prevalence and effect on lipid parameters in normal Han Chinese population. Fragments of ApoE gene forth exon containing codon 112 and 158 polymorphic locus were amplified by PCR, and then digested with Cfo I endonuclease. Genotypes and alleles frequencies of 168 healthy Han Chinese were calculated. The frequency of genotypes epsilon3/3, epsilon3/4, and epsilon2/3 was found to be 75.00, 10.70, and 11.90%, respectively, and 0.60, 1.20, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
12
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
10
12
1
Order By: Relevance
“…Our analysis indicates that the ε4 allele frequency was significantly increased in T2DM patients with macrovascular complications. In contrast, healthy individuals more frequently possessed the ε3 allele (60%), similar to reports of allele frequencies in similar healthy populations (13). The amino acid changes between APOE2, APOE3, and APOE4 are enough to reduce the receptor binding activity of ε2 to only 2% that of ε3 (14).…”
Section: Discussionsupporting
confidence: 83%
“…Our analysis indicates that the ε4 allele frequency was significantly increased in T2DM patients with macrovascular complications. In contrast, healthy individuals more frequently possessed the ε3 allele (60%), similar to reports of allele frequencies in similar healthy populations (13). The amino acid changes between APOE2, APOE3, and APOE4 are enough to reduce the receptor binding activity of ε2 to only 2% that of ε3 (14).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, genotype ɛ3/ɛ3 accounted for 69.04%, followed by ɛ3/ɛ4 (16.19%), ɛ2/ɛ3 (11.60%), ɛ2/ɛ4 (1.35%), ɛ4/ɛ4 (1.08%), and ɛ2/ɛ2 (0.74%) in all subjects, in which ɛ3 had the greatest allele frequency (82.93%), followed by ɛ4 (9.85%) and ɛ2 (7.22%). It showed that the frequencies of APOE allele in the Hakka population were similar to those in the Chinese‐Northeast, Chinese‐Jiangsu Han, and Chinese‐Kunming Han populations, in which ɛ4 allele in the Hakka population was lower than in the Chinese‐Shanghai population . Comparison of our results to the geographically neighboring countries showed that the frequency of ɛ4 allele in the Hakka population was lower than in the Japanese, Mongolian, Vietnamese, Malay, Javanese, and Korean populations, in which ɛ4 gene carriers have a higher risk of cardiovascular disease …”
Section: Discussionsupporting
confidence: 66%
“…However, there is great ethnic variation in APOE frequencies. The frequency of the APOE-ε4 allele in our population is 9.3%, which is in the range of that in Asian (including Chinese) populations (6.3-9.3%) [42,43,44], but lower than that in Caucasian and African American populations (11-27%) [45]. Multivariate analyses did not explore the presence of APOE-ε4 as an independent risk factor of dementia.…”
Section: Discussioncontrasting
confidence: 58%